Multifunctional bipolar plate of zinc-bromine flow battery as well as preparation method and application of multifunctional bipolar plate

By using polyaniline and cyclodextrin polymer modification layers on the bipolar plates of zinc-bromine flow batteries, the problems of slow positive electrode reaction and zinc dendrite growth in zinc-bromine flow batteries were solved, improving the coulombic efficiency and stability of the batteries and extending their service life.

CN121307076APending Publication Date: 2026-01-09HUANENG HEZHANG WIND POWER CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511321025.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-16
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing zinc-bromine flow batteries suffer from slow Br2/Br- reaction at the positive electrode, high polarization, and bromine shuttle, as well as zinc dendrite growth, hydrogen evolution side reaction, and short circuit problems at the negative electrode, resulting in poor battery performance and short lifespan.

Method used

Bipolar plates are modified with polyaniline and cyclodextrin polymers to improve battery performance through physical barrier and chemical adsorption mechanisms. Polyaniline forms a dense coating layer on the positive electrode side to block bromine from contacting the substrate, while cyclodextrin polymers form a cross-linked network on the negative electrode side to restrict zinc ion distribution. Nafion's sulfonic acid groups form directional ion channels, working synergistically to enhance battery performance.

Benefits of technology

It effectively inhibits bromide ion penetration and zinc dendrite growth, improves coulombic efficiency and battery stability, reduces polarization voltage, and extends battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a zinc-bromine flow battery multifunctional bipolar plate and a preparation method and application thereof.The method comprises the steps that polyaniline is added into a cetyltrimethylammonium bromide ethanol solution, after stirring and ultrasonic treatment, a mixed solution is obtained and sprayed to the positive electrode side of a pretreated polypropylene bipolar plate, and after drying, the zinc-bromine flow battery multifunctional bipolar plate is obtained; the polyaniline modified polypropylene bipolar plate is obtained; the preparation method comprises the following steps: dissolving beta-cyclodextrin in a NaOH solution, adding epoxy chloropropane, stirring for reaction, washing to be neutral, drying, grinding and sieving to obtain a cyclodextrin polymer, dispersing the cyclodextrin polymer in a Nafion solution to obtain a cyclodextrin polymer solution, spraying the cyclodextrin polymer solution on the negative electrode side of a polyaniline modified polypropylene bipolar plate, and drying to obtain the multifunctional bipolar plate of the zinc-bromine flow battery. Polyaniline is loaded on the positive electrode side of the bipolar plate to reduce a bromine permeation source and bromine reaction activation energy, a cyclodextrin polymer Nafion solution is used for modifying and stabilizing the pH value of an electrolyte on the negative electrode side, uniform and compact deposition of zinc is promoted, formation of sharp dendrites is reduced, and the electrochemical performance and long-term stability of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical energy storage technology, specifically relating to a multifunctional bipolar plate for a zinc-bromine flow battery, its preparation method, and its application. Background Technology

[0002] With the increasing prominence of clean energy, the demand for energy storage technologies is becoming more diversified. Flow batteries, as a highly efficient and sustainable medium- to long-term energy storage technology, have attracted considerable attention. Zinc-bromine flow batteries, due to their high energy density, low cost, and environmental friendliness, are an important branch of flow batteries. However, existing zinc-bromine flow batteries use bromine / bromine (Br2 / Br4) as the cathode material. - The conversion reaction rate is slow, involves multiple steps, and requires high activation energy. Usually, a complexing agent is added to the positive electrode to complex Br2 to improve solubility, but this makes the Br2 reaction pathway more complicated. The slow Br2 reaction becomes a bottleneck in the overall battery performance, resulting in high polarization voltage, significantly reducing voltage efficiency and power density, leading to low energy efficiency, limited power density, and low coulombic efficiency.

[0003] A significant challenge in zinc-bromine flow batteries is the formation of zinc dendrites at the negative electrode. During zinc deposition, influenced by the microenvironment at the electrode-electrolyte interface, the reduced zinc tends to preferentially grow along specific crystal orientations, ultimately forming dendritic structures with a tree-like morphology. As charge-discharge cycles continue, these zinc dendrites grow along the kinetically dominant direction, significantly reducing the interfacial stability of the electrochemical system. When the zinc dendrites grow to a critical size, their tips penetrate the separator, causing damage to the internal battery structure and triggering a series of irreversible battery failure mechanisms. On one hand, the bromine at the positive electrode shuttles through the punctured separator, drastically reducing the coulombic efficiency of the zinc-bromine flow battery and severely impacting its performance. On the other hand, contact between zinc dendrites and the positive electrode can cause short circuits, directly leading to battery failure. This severely limits the lifespan and stability of zinc-bromine flow batteries, becoming a key factor hindering their widespread application.

[0004] Therefore, developing a multifunctional bipolar plate for zinc-bromine flow batteries and its preparation method is of great significance for improving the performance of zinc-bromine flow batteries and promoting their practical application. Summary of the Invention

[0005] To overcome the shortcomings of the prior art, the present invention aims to provide a multifunctional bipolar plate for zinc-bromine flow batteries, its preparation method, and its application, thereby solving the problem of the Br2 / Br content of the positive electrode in existing zinc-bromine flow batteries. - Technical issues include slow reaction, high polarization and bromine shuttle, as well as zinc dendrite growth at the negative electrode, hydrogen evolution side reaction and battery short circuit.

[0006] To achieve the above objectives, the present invention employs the following technical solution: This invention discloses a method for preparing a multifunctional bipolar plate for a zinc-bromine flow battery, comprising: 1) Pretreatment of polypropylene bipolar plates; 2) Add polyaniline to a hexadecyltrimethylammonium bromide ethanol solution, stir and sonicate to obtain a mixed solution, spray the mixed solution onto the positive electrode side of the pretreated polypropylene bipolar plate, and dry to obtain a polyaniline-modified polypropylene bipolar plate. 3) Dissolve β-cyclodextrin in NaOH solution, add epichlorohydrin, stir and react, wash until neutral, dry, grind and sieve to obtain cyclodextrin polymer; disperse the cyclodextrin polymer in Nafion solution to obtain cyclodextrin polymer solution; spray the cyclodextrin polymer solution onto the negative electrode side of polyaniline-modified polypropylene bipolar plate, and dry to obtain a multifunctional bipolar plate for zinc-bromine flow batteries.

[0007] Preferably, in step 1), the pretreatment includes: ultrasonically cleaning the polypropylene bipolar plate with ethanol or deionized water for 15-30 min, and drying it at 40-60℃ for 12-24 h.

[0008] Preferably, in step 2), the molar concentration of polyaniline in the mixed solution is 0.1-0.3 mol / L.

[0009] Preferably, in step 2), the stirring time is 30-60 min; the ultrasonic time is 0.5-1.5 h; and the drying conditions are drying at 60-80℃ for 6-12 h.

[0010] Preferably, in step 2), the spraying conditions include: a spray velocity of 5-10 mL / min and a spraying time of 5-10 min.

[0011] Preferably, in step 3), 2.0-6.0 g of cyclodextrin polymer is added to every 100 mL of 5% Nafion solution.

[0012] Preferably, in step 3), the stirring reaction conditions are: stirring reaction at 50°C for 16 hours; the drying conditions are: drying at 80°C for 12 hours.

[0013] Preferably, in step 3), the spraying conditions include: a spraying speed of 5-10 mL / min and a spraying time of 5-10 min; the drying conditions are: drying at 60-80℃ for 6-12 h.

[0014] The present invention also discloses a multifunctional bipolar plate for zinc-bromine flow batteries, which is prepared by the above-mentioned method for preparing multifunctional bipolar plates for zinc-bromine flow batteries.

[0015] The present invention also discloses the application of the multifunctional bipolar plate of the zinc-bromine flow battery prepared by the above-mentioned method in the zinc-bromine flow battery. The coulombic efficiency of the zinc-bromine flow battery is 91.5%-95.6%; the energy efficiency is 75.76%-81.94%; and the voltage efficiency is 82.8%-85.8%.

[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention discloses a method for preparing a multifunctional bipolar plate for a zinc-bromine flow battery. A polyaniline coating on the positive electrode side physically covers the bipolar plate surface through a benzene ring structure, blocking bromine contact with the substrate. On the negative electrode side, a cyclodextrin polymer network homogenizes zinc ion distribution through weak coordination of hydroxyl groups, while the sulfonic acid groups of Nafion form directional ion channels, restricting the zinc deposition direction. The synergistic effect of the positive and negative electrode modification layers spatially separates the bromine barrier and zinc regulation functions, improving battery performance through a dual mechanism of physical barrier and chemical adsorption. This effectively suppresses the self-discharge phenomenon caused by bromine ion penetration into the bipolar plate and reduces the corrosion rate of bromine on the carbon substrate. Simultaneously, it guides zinc ions to deposit uniformly along the direction parallel to the substrate, reducing the risk of dendrite puncture. The synergistic effect of the dual-functional coating stabilizes the electrolyte pH and suppresses hydrogen evolution side reactions, thereby improving the battery's coulombic efficiency and cycle stability.

[0017] Furthermore, during surface pretreatment, the micro-jets generated by ultrasonic cavitation can penetrate the micron-level pores of the bipolar plate, stripping away particulate contaminants adhering to the trenches. The cleaning medium is selected based on the differences in contaminant composition: ethanol preferentially removes oily residues, while deionized water targets water-soluble impurities. The drying stage is controlled by gradient temperature increases, with surface moisture slowly evaporating at an initial temperature of 40°C, and the final temperature of 60°C accelerating solvent evaporation from the internal pores. A minimum drying time of 12 hours ensures complete drying of the 3mm thick bipolar plate, providing an ideal adhesion interface for subsequent coatings.

[0018] Furthermore, when the polyaniline concentration is below 0.1 mol / L, the number of polyaniline molecules adsorbed per unit area is insufficient, making it difficult to form a continuous covering modification layer, resulting in a decrease in bromine barrier effect. When the concentration exceeds 0.3 mol / L, the van der Waals forces between polyaniline molecules increase, disrupting the dispersion stability in surfactant micelles and forming irreversible aggregates. By precisely controlling the concentration within the range of 0.1-0.3 mol / L, the micelle structure of hexadecyltrimethylammonium bromide can effectively encapsulate polyaniline molecules, forming a stable dispersion system under ultrasonic assistance. During spraying, surfactant molecules are oriented on the surface of the bipolar plate, driving the uniform distribution of polyaniline to form a dense adsorption layer, achieving an optimized balance between intermolecular distance and conductive network. This achieves a uniform distribution of the polyaniline modification layer on the positive electrode side of the bipolar plate, forming a continuous and dense bromine barrier. It ensures the effective dispersion of polyaniline by surfactant micelles, maintains a suitable viscosity of the spray liquid, and ensures the uniformity of the modification layer thickness. This improves the efficiency of bromide ion migration blocking while maintaining a stable electron conduction path, ultimately improving the bromine reaction kinetics of the battery.

[0019] Furthermore, during mechanical stirring of the mixed solution for 30-60 minutes, surfactant molecules fully encapsulate the polyaniline particles, forming a stable colloidal system. Subsequent ultrasonic treatment for 0.5-1.5 hours dissociates the aggregates into a nanoscale dispersed phase, forming a uniform suspension. After spraying, drying at 60-80℃ for 6-12 hours allows solvent molecules to slowly evaporate, forming a crack-free, continuous conductive film layer. This enables the polyaniline particles to form a three-dimensional interpenetrating network structure on the bipolar plate surface. This solves the problem of easy agglomeration and detachment of the polyaniline modification layer, forming a functional interface layer with a stable conductive network. This allows the bipolar plate to maintain stable bromine barrier capability and charge transport efficiency during long-term charge-discharge cycles, laying a material foundation for improving the overall performance of zinc-bromine flow batteries.

[0020] Furthermore, by limiting the parameter combination of 5-10 mL / min and 5-10 min, a dynamic balance was achieved between the deposition rate per unit area and the solvent evaporation rate, thus realizing the directional structural control of the polyaniline modified layer on the positive electrode side of the bipolar plate. This effectively controlled the wetting and spreading process of the solution on the substrate surface, causing the polyaniline molecules to form a chain-like arrangement perpendicular to the substrate direction, significantly enhancing the bromide ion blocking ability and electronic conduction efficiency.

[0021] Furthermore, the hydroxyl groups of the cyclodextrin polymer and the sulfonic acid groups of Nafion form a composite network structure through hydrogen bonding. The cyclodextrin cavities in this network structure restrict the disordered migration of zinc ions through steric hindrance, while the sulfonic acid groups of Nafion form directional ion channels. During deposition, zinc ions must sequentially pass through the cyclodextrin cavities and sulfonic acid channel channels, their diffusion path being constrained within a two-dimensional space parallel to the substrate plane. This synergistic mechanism effectively inhibits the three-dimensional aggregation of zinc ions on the electrode surface, promoting uniform layered deposition of metallic zinc. This achieves directional control of the zinc deposition path, effectively suppressing dendrite tip growth and reducing stress concentration on the electrode surface. Simultaneously, the formed composite film has a pH buffering function, suppressing interfacial hydrogen evolution side reactions and extending electrode cycle life. This synergistic modification mechanism increases the density of the zinc deposition layer, enhances the stability of the electrode / electrolyte interface, and improves the reversibility of the battery charge-discharge process.

[0022] Furthermore, under isothermal conditions of 50℃, the epoxy groups of epichlorohydrin gradually undergo a condensation reaction with the hydroxyl groups on β-cyclodextrin molecules. By extending the reaction time to 16 hours, the cross-linking reaction is ensured to be fully completed, forming a cyclodextrin polymer with a stable network structure. During this process, temperature control avoids excessive breakage of intramolecular hydrogen bonds in β-cyclodextrin molecules, maintaining the integrity of its cavity structure. Subsequent drying at 80℃ for 12 hours completely removes moisture and residual solvent, while preserving the nanoscale pores formed within the polymer. This provides a structural basis for maintaining the permeability of ion channels during subsequent composite with Nafion solution. Controllable synthesis and functional maintenance of the cross-linked structure of the cyclodextrin polymer were achieved, ensuring that the product has a uniform nanopore distribution and a stable chemical structure. This provides a structurally complete cyclodextrin polymer raw material for the subsequent preparation of composite coatings that inhibit zinc dendrite growth.

[0023] Furthermore, with a spray velocity of 5-10 mL / min, the solution forms a uniform liquid film covering the substrate surface, avoiding droplet splashing due to excessive flow rate or local accumulation due to excessive flow rate. The spraying time of 5-10 min, linearly related to the spray velocity, ensures that the mass of the cyclodextrin polymer-Nafion composite deposited per square centimeter of substrate surface reaches a predetermined threshold. Maintaining a drying temperature of 60-80℃ allows Nafion molecular chains to gain sufficient kinetic energy for orderly arrangement, while the cross-linked network structure of the cyclodextrin polymer is fully preserved. Controlling the drying time to 6-12 h allows solvent molecules to fully escape, forming a dense structure within the coating and achieving stable interfacial bonding strength. This achieves uniform coverage of the cyclodextrin polymer-Nafion composite coating, enhancing the interfacial bonding strength between the coating and the substrate. The orderliness of the coating's microstructure is improved, the zinc ion deposition path is effectively controlled, and the electrolyte pH stability is significantly improved. This solves the coating performance fluctuation problem caused by spray parameter mismatch in traditional processes, providing a reliable method for negative electrode side modification of zinc-bromine flow battery bipolar plates.

[0024] This invention also discloses the preparation method of the aforementioned multifunctional bipolar plate for zinc-bromine flow batteries. The multifunctional bipolar plate for zinc-bromine flow batteries, prepared by a polyaniline modification layer, forms a dual physicochemical barrier mechanism on the positive electrode side: the benzene ring structure of polyaniline adsorbs onto the carbon substrate surface through π-π interactions, forming a dense covering layer that blocks direct corrosion of the substrate by bromine; its quinone structure reversibly adsorbs bromine molecules through redox reactions, accelerating the electron transfer rate of bromine and reducing the activation energy of the reaction. Simultaneously, the positive charge carried by the polyaniline backbone inhibits the migration of bromine ions to the negative electrode side through electrostatic repulsion, reducing capacity decay caused by bromine permeation. On the negative electrode side, the cross-linked network of the cyclodextrin polymer forms three-dimensional nanochannels, restricting zinc ions to diffuse only in the direction parallel to the substrate, promoting uniform zinc deposition; its surface hydroxyl groups adsorb hydrogen ions through weak coordination, inhibiting the increase of interfacial pH and reducing hydrogen evolution side reactions. The sulfonic acid groups of Nafion form continuous ion channels, guiding zinc ions to migrate along specific paths, synergistically regulating the zinc deposition morphology with the confinement effect of cyclodextrin, and inhibiting dendrite formation.

[0025] This invention also discloses the application of the multifunctional bipolar plate for zinc-bromine flow batteries prepared by the above-mentioned method in zinc-bromine flow batteries. On the positive electrode side, the polyaniline-modified layer forms a dense covering layer through π-π interactions with the carbon substrate via a benzene ring structure, blocking direct contact between bromine and the carbon substrate. Simultaneously, the positive charge generated by its protonated amino groups inhibits the transmembrane migration of bromine anions through electrostatic repulsion. The quinone structure adsorbs dissolved bromine molecules through a reversible redox reaction, reducing the activation energy of the bromine reaction and accelerating electron transfer. On the negative electrode side, the cross-linked network of the cyclodextrin polymer and the ion channels of Nafion form a composite structure. The sulfonic acid groups provide a continuous proton conduction path, preventing proton depletion at the interface, while the hydroxyl groups of the cyclodextrin stabilize the interfacial proton concentration through weak adsorption. The nanoscale pores in the cross-linked network create a steric hindrance effect, forcing zinc ions to diffuse in a two-dimensional direction parallel to the substrate, inhibiting three-dimensional dendrite growth. The synergistic effect of the positive and negative electrode modification layers is manifested in the following ways: the reduced bromine permeation on the positive electrode side decreases the probability of side reactions in the zinc negative electrode, while the stable deposition behavior on the negative electrode side, in turn, reduces the irreversible consumption of bromine on the positive electrode side, forming a virtuous cycle. This effectively suppresses the self-discharge phenomenon caused by bromine anion penetration through the bipolar plate, reduces local current density fluctuations during zinc deposition, and avoids hydrogen evolution side reactions caused by sudden changes in interface pH. The positive electrode modification layer extends the corrosion resistance life of the carbon substrate while maintaining high conductivity, while the composite structure on the negative electrode side guides uniform zinc deposition while maintaining proton transport efficiency. The synergistic effect of the two functional layers enables the battery to maintain a stable ion transport path and reaction interface during charge-discharge cycles, achieving a comprehensive improvement in efficiency indicators and a significant extension of cycle life. Detailed Implementation

[0026] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0027] Unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined to form new technical solutions.

[0028] Unless otherwise specified, all the technical features and preferred features mentioned herein can be combined to form new technical solutions.

[0029] In this invention, unless otherwise specified, percentage (%) or parts refer to weight percentage or parts relative to the composition.

[0030] Unless otherwise specified, the components or preferred components involved in this invention can be combined with each other to form new technical solutions.

[0031] In this invention, unless otherwise specified, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "6~22" indicates that all real numbers between "6~22" have been listed in this document, and "6~22" is simply a shortened representation of these numerical combinations.

[0032] The "scope" disclosed in this invention can be in the form of a lower limit and an upper limit, and can be one or more lower limits and one or more upper limits, respectively.

[0033] In this invention, the term "and / or" as used herein refers to any combination of one or more of the associated listed items, as well as all possible combinations, and includes such combinations.

[0034] In this invention, unless otherwise stated, the various reactions or operation steps may be performed sequentially or in a particular order. Preferably, the reaction methods described herein are performed sequentially.

[0035] Unless otherwise stated, the technical and scientific terms used herein have the same meanings as those familiar to those skilled in the art. Furthermore, any methods or materials similar to or equivalent to those described herein may also be used in this invention.

[0036] This invention provides a method for preparing a multifunctional bipolar plate for a zinc-bromine flow battery, comprising the following steps: 1) Pretreatment of PP bipolar plates The polypropylene bipolar plate (PP bipolar plate) is cleaned by ultrasonic cleaning with ethanol or deionized water for 15-30 minutes to remove impurities and contaminants from the surface. Then, it is dried in a vacuum drying oven at 40-60℃ for 12-24 hours for later use.

[0037] 2) Modification of the positive electrode side of PP bipolar plates Prepare a 30 mmol / L hexadecyltrimethylammonium bromide ethanol solution. Use hexadecyltrimethylammonium bromide as a surfactant to improve the dispersibility of hydrophobic polyaniline in ethanol. Then add polyaniline and stir magnetically for 30-60 min. Place the solution in an ice-water bath ultrasonic cleaner and sonicate for 0.5-1.5 h to finally achieve a polyaniline concentration of 0.1-0.3 mol / L in the mixed solution.

[0038] Take 50 mL of each of the above mixed solutions and spray the suspension evenly onto the positive electrode side of a PP bipolar plate of the same size using a spray gun. The spraying speed is 5-10 mL / min and the spraying time is 5-10 min. Place the sprayed PP bipolar plate in a vacuum drying oven and dry it at 60-80℃ for 6-12 h to complete the modification of the positive electrode side of the PP bipolar plate with polyaniline, and obtain the polyaniline-modified PP bipolar plate.

[0039] 3) Modification of the negative electrode side of PP bipolar plate 31) Synthesis of cyclodextrin polymers (PCDs) A certain amount of β-cyclodextrin was dissolved in a 30% NaOH solution and stirred in an ice-water bath until the β-cyclodextrin dissolved. Epichlorohydrin was then slowly added dropwise. After the addition was complete, the ice-water bath was removed, the temperature was slowly raised to 50°C, and the mixture was stirred for 16 hours. After the reaction was completed, the mixture was cooled to room temperature and washed repeatedly with a large amount of deionized water until the washing solution was close to neutral. Finally, the wet cyclodextrin polymer was dried in an 80°C oven for 12 hours, and then ground and sieved to obtain cyclodextrin polymer powder.

[0040] 32) Negative electrode side modification of polyaniline-modified PP bipolar plates A certain amount of cyclodextrin polymer powder was weighed and dispersed in a 5% (w / w) Nafion solution to form cyclodextrin polymer solutions of different concentrations. 50 mL of each of the above mixed solutions was taken and uniformly sprayed onto the negative electrode side of a polyaniline-modified PP bipolar plate using a spray gun. The spraying speed was 5-10 mL / min, and the spraying time was 5-10 min. The sprayed PP bipolar plate was then placed in a vacuum drying oven and dried at 60-80℃ for 6-12 h to obtain a multifunctional bipolar plate for zinc-bromine flow batteries.

[0041] This invention involves loading polyaniline onto the positive electrode side of a PP bipolar plate. Polyaniline can block the anion Br3 through electrostatic repulsion. - and Br - The migration of bromine effectively prevents bromine permeation, reduces side reactions, improves coulombic efficiency, and significantly reduces capacity loss. The quinone structure of polyaniline reversibly adsorbs Br2, accelerating electron transfer and significantly reducing the activation energy, thus improving battery charge / discharge efficiency. The benzene ring structure of polyaniline adsorbs on the carbon surface, blocking direct contact between bromine and carbon, thereby protecting the bipolar plate from corrosion and extending its lifespan. In this invention, when the negative electrode side of a polyaniline-modified PP bipolar plate is modified with a cyclodextrin polymer Nafion solution, Nafion accelerates H2 migration, effectively preventing bromine permeation, reducing side reactions, improving coulombic efficiency, and significantly reducing capacity loss. + Diffusion from the electrode surface into the electrolyte bulk avoids interfacial H +The resulting pH increase due to depletion inhibits the hydrogen evolution reaction and improves the long-term cycle stability of the battery. In this invention, when the negative electrode side of a polyaniline-modified PP bipolar plate is modified with a cyclodextrin polymer Nafion solution, the hydroxyl groups of the cyclodextrin polymer can weakly adsorb H₂. + This forms a pH-stable interface, improving the long-term cycle stability of the battery. The sulfonic acid groups of Nafion form uniform ion channels, guiding Zn... 2+ Orderly deposition along the bipolar plate surface promotes more uniform and dense zinc deposition, reduces the formation of sharp dendrites, and improves electrode stability and cycle life. The hydroxyl groups in the cyclodextrin polymer crosslinking network are negatively charged in the electrolyte, which can homogenize the electric field distribution and promote Zn deposition. 2+ Uniform distribution prevents zinc dendrite formation, improving electrode stability and cycle life. The nanochannels of the cyclodextrin polymer confine Zn... 2+ Diffusion is limited to the direction parallel to the substrate, promoting more uniform and dense zinc deposition, reducing the formation of sharp dendrites, and improving electrode stability and cycle life. The synergistic effect of polyaniline, cyclodextrin polymer, and Nafion enables the zinc-bromine flow battery to exhibit better electrochemical performance.

[0042] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Therefore, the detailed description of the embodiments of the present invention provided below is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0043] Example 1 A method for preparing a multifunctional bipolar plate for a zinc-bromine flow battery, comprising: The PP bipolar plates are cleaned by ultrasonic cleaning with ethanol for 15 minutes to remove surface impurities and contaminants, and then dried in a vacuum drying oven at 40°C for 12 hours for later use.

[0044] Weigh 1.09 g of cetyltrimethylammonium bromide and place it in 50 mL of 75% ethanol. Then add 2.00 g of polyaniline and bring the volume to 100 mL. Stir magnetically for 30 min and then place the solution in an ice-water bath ultrasonic cleaner and sonicate for 0.5 h. Finally, the concentration of polyaniline in the mixed solution is 0.1 mol / L.

[0045] Take 50 mL of the above mixed solution and spray the suspension evenly onto the positive electrode side of a PP bipolar plate of the same size using a spray gun. The spraying speed is 5 mL / min and the spraying time is 10 min. Place the sprayed PP bipolar plate in a vacuum drying oven and dry it at 70℃ for 8 h to complete the modification of the positive electrode side of the PP bipolar plate with polyaniline, and obtain the polyaniline-modified PP bipolar plate.

[0046] Example 2 A method for preparing a multifunctional bipolar plate for a zinc-bromine flow battery, comprising: The PP bipolar plates are cleaned by ultrasonic cleaning with ethanol for 15 minutes to remove surface impurities and contaminants, and then dried in a vacuum drying oven at 40°C for 12 hours for later use.

[0047] Weigh 1.09 g of cetyltrimethylammonium bromide and place it in 50 mL of 75% ethanol. Then add 4.00 g of polyaniline and bring the volume to 100 mL. Stir magnetically for 30 min and then place the solution in an ice-water bath ultrasonic cleaner and sonicate for 0.5 h. Finally, the concentration of polyaniline in the mixed solution is 0.2 mol / L.

[0048] Take 50 mL of the above mixed solution and spray the suspension evenly onto the positive electrode side of a PP bipolar plate of the same size using a spray gun. The spraying speed is 5 mL / min and the spraying time is 10 min. Place the sprayed PP bipolar plate in a vacuum drying oven and dry it at 70℃ for 8 h to complete the modification of the positive electrode side of the PP bipolar plate with polyaniline, and obtain the polyaniline-modified PP bipolar plate.

[0049] Example 3 A method for preparing a multifunctional bipolar plate for a zinc-bromine flow battery, comprising: The PP bipolar plates are cleaned by ultrasonic cleaning with ethanol for 15 minutes to remove surface impurities and contaminants, and then dried in a vacuum drying oven at 40°C for 12 hours for later use.

[0050] Weigh 1.09 g of cetyltrimethylammonium bromide and place it in 50 mL of 75% ethanol. Then add 6.00 g of polyaniline and bring the volume to 100 mL. Stir magnetically for 30 min and then place the solution in an ice-water bath ultrasonic cleaner and sonicate for 0.5 h. Finally, the concentration of polyaniline in the mixed solution is 0.3 mol / L.

[0051] Take 50 mL of the above mixed solution and spray the suspension evenly onto the positive electrode side of a PP bipolar plate of the same size using a spray gun. The spraying speed is 5 mL / min and the spraying time is 10 min. Place the sprayed PP bipolar plate in a vacuum drying oven and dry it at 70℃ for 8 h to complete the modification of the positive electrode side of the PP bipolar plate with polyaniline, and obtain the polyaniline-modified PP bipolar plate.

[0052] Example 4 A method for preparing a multifunctional bipolar plate for a zinc-bromine flow battery, comprising: The PP bipolar plates are cleaned by ultrasonic cleaning with ethanol for 15 minutes to remove surface impurities and contaminants, and then dried in a vacuum drying oven at 40°C for 12 hours for later use.

[0053] Weigh 1.09 g of cetyltrimethylammonium bromide and place it in 50 mL of 75% ethanol. Then add 6.00 g of polyaniline and bring the volume to 100 mL. Stir magnetically for 30 min and then place the solution in an ice-water bath ultrasonic cleaner and sonicate for 0.5 h. Finally, the concentration of polyaniline in the mixed solution is 0.3 mol / L.

[0054] Take 50 mL of the above mixed solution and spray the suspension evenly onto the positive electrode side of a PP bipolar plate of the same size using a spray gun. The spraying speed is 10 mL / min and the spraying time is 5 min. Place the sprayed PP bipolar plate in a vacuum drying oven and dry it at 70℃ for 8 h to complete the modification of the positive electrode side of the PP bipolar plate with polyaniline, and obtain the polyaniline-modified PP bipolar plate.

[0055] Example 5 A method for preparing a multifunctional bipolar plate for a zinc-bromine flow battery, comprising: The PP bipolar plates are cleaned by ultrasonic cleaning with ethanol for 15 minutes to remove surface impurities and contaminants, and then dried in a vacuum drying oven at 40°C for 12 hours for later use.

[0056] Weigh 1.09 g of cetyltrimethylammonium bromide and place it in 50 mL of 75% ethanol. Then add 6.00 g of polyaniline and bring the volume to 100 mL. Stir magnetically for 30 min and then place the solution in an ice-water bath ultrasonic cleaner and sonicate for 0.5 h. Finally, the concentration of polyaniline in the mixed solution is 0.3 mol / L.

[0057] Take 50 mL of the above mixed solution and spray the suspension evenly onto the positive electrode side of a PP bipolar plate of the same size using a spray gun. The spraying speed is 10 mL / min and the spraying time is 5 min. Place the sprayed PP bipolar plate in a vacuum drying oven and dry it at 70℃ for 8 h to complete the modification of the positive electrode side of the PP bipolar plate with polyaniline, and obtain the polyaniline-modified PP bipolar plate.

[0058] Weigh 10g of β-cyclodextrin and dissolve it in 50mL of 30% NaOH solution. Stir in an ice-water bath until the β-cyclodextrin dissolves. Then, slowly add epichlorohydrin dropwise. After the addition is complete, remove the ice-water bath, slowly raise the temperature to 50℃, and stir the reaction for 16h. After the reaction is complete, cool the mixture to room temperature and wash it repeatedly with a large amount of deionized water until the pH of the washing solution is 7. Finally, place the wet cyclodextrin polymer in an 80℃ oven to dry for 12h. Finally, grind and sieve to obtain cyclodextrin polymer powder.

[0059] Weigh 2.0 g of cyclodextrin polymer and disperse it in 100 mL of 5% Nafion solution. Take 50 mL of the mixed solution and spray the suspension evenly onto the negative electrode side of the polyaniline-modified PP bipolar plate using a spray gun. The spraying speed is 5 mL / min, and the spraying time is 10 min. Place the sprayed PP bipolar plate in a vacuum drying oven and dry it at 70 °C for 8 h to obtain the multifunctional PP bipolar plate.

[0060] Example 6 A method for preparing a multifunctional bipolar plate for a zinc-bromine flow battery, comprising: The PP bipolar plates are cleaned by ultrasonic cleaning with ethanol for 15 minutes to remove surface impurities and contaminants, and then dried in a vacuum drying oven at 40°C for 12 hours for later use.

[0061] Weigh 1.09 g of cetyltrimethylammonium bromide and place it in 50 mL of 75% ethanol. Then add 6.00 g of polyaniline and bring the volume to 100 mL. Stir magnetically for 30 min and then place the solution in an ice-water bath ultrasonic cleaner and sonicate for 0.5 h. Finally, the concentration of polyaniline in the mixed solution is 0.3 mol / L.

[0062] Take 50 mL of the above mixed solution and spray the suspension evenly onto the positive electrode side of a PP bipolar plate of the same size using a spray gun. The spraying speed is 10 mL / min and the spraying time is 5 min. Place the sprayed PP bipolar plate in a vacuum drying oven and dry it at 70℃ for 8 h to complete the modification of the positive electrode side of the PP bipolar plate with polyaniline, and obtain the polyaniline-modified PP bipolar plate.

[0063] Weigh 10g of β-cyclodextrin and dissolve it in 50mL of 30% NaOH solution. Stir in an ice-water bath until the β-cyclodextrin dissolves. Then, slowly add epichlorohydrin dropwise. After the addition is complete, remove the ice-water bath, slowly raise the temperature to 50℃, and stir the reaction for 16h. After the reaction is complete, cool the mixture to room temperature and wash it repeatedly with a large amount of deionized water until the pH of the washing solution is 7. Finally, place the wet cyclodextrin polymer in an 80℃ oven to dry for 12h. Finally, grind and sieve to obtain cyclodextrin polymer powder.

[0064] Weigh 4.0 g of cyclodextrin polymer and disperse it in 100 mL of 5% Nafion solution. Take 50 mL of the mixed solution and spray the suspension evenly onto the negative electrode side of the polyaniline-modified PP bipolar plate using a spray gun. The spraying speed is 5 mL / min, and the spraying time is 10 min. Place the sprayed PP bipolar plate in a vacuum drying oven and dry it at 70 °C for 8 h to obtain the multifunctional PP bipolar plate.

[0065] Example 7 A method for preparing a multifunctional bipolar plate for a zinc-bromine flow battery, comprising: The PP bipolar plates are cleaned by ultrasonic cleaning with ethanol for 15 minutes to remove surface impurities and contaminants, and then dried in a vacuum drying oven at 40°C for 12 hours for later use.

[0066] Weigh 1.09 g of cetyltrimethylammonium bromide and place it in 50 mL of 75% ethanol. Then add 6.00 g of polyaniline and bring the volume to 100 mL. Stir magnetically for 30 min and then place the solution in an ice-water bath ultrasonic cleaner and sonicate for 0.5 h. Finally, the concentration of polyaniline in the mixed solution is 0.3 mol / L.

[0067] Take 50 mL of the above mixed solution and spray the suspension evenly onto the positive electrode side of a PP bipolar plate of the same size using a spray gun. The spraying speed is 10 mL / min and the spraying time is 5 min. Place the sprayed PP bipolar plate in a vacuum drying oven and dry it at 70℃ for 8 h to complete the modification of the positive electrode side of the PP bipolar plate with polyaniline, and obtain the polyaniline-modified PP bipolar plate.

[0068] Weigh 10g of β-cyclodextrin and dissolve it in 50mL of 30% NaOH solution. Stir in an ice-water bath until the β-cyclodextrin dissolves. Then, slowly add epichlorohydrin dropwise. After the addition is complete, remove the ice-water bath, slowly raise the temperature to 50℃, and stir the reaction for 16h. After the reaction is complete, cool the mixture to room temperature and wash it repeatedly with a large amount of deionized water until the pH of the washing solution is 7. Finally, place the wet cyclodextrin polymer in an 80℃ oven to dry for 12h. Finally, grind and sieve to obtain cyclodextrin polymer powder.

[0069] Weigh 6.0 g of cyclodextrin polymer and disperse it in 100 mL of 5% Nafion solution. Take 50 mL of the mixed solution and spray the suspension evenly onto the negative electrode side of the polyaniline-modified PP bipolar plate using a spray gun. The spraying speed is 5 mL / min, and the spraying time is 10 min. Place the sprayed PP bipolar plate in a vacuum drying oven and dry it at 70 °C for 8 h to obtain the multifunctional PP bipolar plate.

[0070] Example 8 A method for preparing a multifunctional bipolar plate for a zinc-bromine flow battery, comprising: The PP bipolar plates are cleaned by ultrasonic cleaning with ethanol for 15 minutes to remove surface impurities and contaminants, and then dried in a vacuum drying oven at 40°C for 12 hours for later use.

[0071] Weigh 1.09 g of cetyltrimethylammonium bromide and place it in 50 mL of 75% ethanol. Then add 6.00 g of polyaniline and bring the volume to 100 mL. Stir magnetically for 30 min and then place the solution in an ice-water bath ultrasonic cleaner and sonicate for 0.5 h. Finally, the concentration of polyaniline in the mixed solution is 0.3 mol / L.

[0072] Take 50 mL of the above mixed solution and spray the suspension evenly onto the positive electrode side of a PP bipolar plate of the same size using a spray gun. The spraying speed is 10 mL / min and the spraying time is 5 min. Place the sprayed PP bipolar plate in a vacuum drying oven and dry it at 70℃ for 8 h to complete the modification of the positive electrode side of the PP bipolar plate with polyaniline, and obtain the polyaniline-modified PP bipolar plate.

[0073] Weigh 10g of β-cyclodextrin and dissolve it in 50mL of 30% NaOH solution. Stir in an ice-water bath until the β-cyclodextrin dissolves. Then, slowly add epichlorohydrin dropwise. After the addition is complete, remove the ice-water bath, slowly raise the temperature to 50℃, and stir the reaction for 16h. After the reaction is complete, cool the mixture to room temperature and wash it repeatedly with a large amount of deionized water until the pH of the washing solution is 7. Finally, place the wet cyclodextrin polymer in an 80℃ oven to dry for 12h. Finally, grind and sieve to obtain cyclodextrin polymer powder.

[0074] Weigh 6.0 g of cyclodextrin polymer and disperse it in 100 mL of 5% Nafion solution. Take 50 mL of the mixed solution and spray the suspension evenly onto the negative electrode side of the polyaniline-modified PP bipolar plate using a spray gun at a spray rate of 10 mL / min for 5 min. Place the sprayed PP bipolar plate in a vacuum drying oven and dry it at 70 °C for 8 h to obtain the multifunctional PP bipolar plate.

[0075] Example 9 A method for preparing a multifunctional bipolar plate for a zinc-bromine flow battery, comprising: The PP bipolar plates are cleaned by ultrasonic cleaning with ethanol for 20 minutes to remove surface impurities and contaminants, and then dried in a vacuum drying oven at 50°C for 16 hours for later use.

[0076] Weigh 1.09 g of cetyltrimethylammonium bromide and place it in 50 mL of 75% ethanol. Then add 6.00 g of polyaniline and bring the volume to 100 mL. Stir magnetically for 40 min and then place the solution in an ice-water bath ultrasonic cleaner and sonicate for 1 h. Finally, the concentration of polyaniline in the mixed solution is 0.3 mol / L.

[0077] Take 50 mL of the above mixed solution and spray the suspension evenly onto the positive electrode side of a PP bipolar plate of the same size using a spray gun. The spraying speed is 10 mL / min and the spraying time is 5 min. Place the sprayed PP bipolar plate in a vacuum drying oven and dry it at 60℃ for 12 h to complete the modification of the positive electrode side of the PP bipolar plate with polyaniline, and obtain the polyaniline-modified PP bipolar plate.

[0078] Weigh 10g of β-cyclodextrin and dissolve it in 50mL of 30% NaOH solution. Stir in an ice-water bath until the β-cyclodextrin dissolves. Then, slowly add epichlorohydrin dropwise. After the addition is complete, remove the ice-water bath, slowly raise the temperature to 50℃, and stir the reaction for 16h. After the reaction is complete, cool the mixture to room temperature and wash it repeatedly with a large amount of deionized water until the pH of the washing solution is 7. Finally, place the wet cyclodextrin polymer in an 80℃ oven to dry for 12h. Finally, grind and sieve to obtain cyclodextrin polymer powder.

[0079] Weigh 6.0 g of cyclodextrin polymer and disperse it in 100 mL of 5% Nafion solution. Take 50 mL of the mixed solution and spray the suspension evenly onto the negative electrode side of the polyaniline-modified PP bipolar plate using a spray gun. The spraying speed is 5 mL / min, and the spraying time is 10 min. Place the sprayed PP bipolar plate in a vacuum drying oven and dry it at 60 °C for 12 h to obtain the multifunctional PP bipolar plate.

[0080] Example 10 A method for preparing a multifunctional bipolar plate for a zinc-bromine flow battery, comprising: The PP bipolar plates are cleaned by ultrasonic cleaning with ethanol for 30 minutes to remove surface impurities and contaminants, and then dried in a vacuum drying oven at 60°C for 24 hours for later use.

[0081] Weigh 1.09 g of cetyltrimethylammonium bromide and place it in 50 mL of 75% ethanol. Then add 6.00 g of polyaniline and bring the volume to 100 mL. Stir magnetically for 60 min and then place the solution in an ice-water bath ultrasonic cleaner and sonicate for 1.5 h. Finally, the concentration of polyaniline in the mixed solution is 0.3 mol / L.

[0082] Take 50 mL of the above mixed solution and spray the suspension evenly onto the positive electrode side of a PP bipolar plate of the same size using a spray gun. The spraying speed is 10 mL / min and the spraying time is 5 min. Place the sprayed PP bipolar plate in a vacuum drying oven and dry it at 80℃ for 6 h to complete the modification of the positive electrode side of the PP bipolar plate with polyaniline, and obtain the polyaniline-modified PP bipolar plate.

[0083] Weigh 10g of β-cyclodextrin and dissolve it in 50mL of 30% NaOH solution. Stir in an ice-water bath until the β-cyclodextrin dissolves. Then, slowly add epichlorohydrin dropwise. After the addition is complete, remove the ice-water bath, slowly raise the temperature to 50℃, and stir the reaction for 16h. After the reaction is complete, cool the mixture to room temperature and wash it repeatedly with a large amount of deionized water until the pH of the washing solution is 7. Finally, place the wet cyclodextrin polymer in an 80℃ oven to dry for 12h. Finally, grind and sieve to obtain cyclodextrin polymer powder.

[0084] Weigh 6.0 g of cyclodextrin polymer and disperse it in 100 mL of 5% Nafion solution. Take 50 mL of the mixed solution and spray the suspension evenly onto the negative electrode side of the polyaniline-modified PP bipolar plate using a spray gun. The spraying speed is 5 mL / min, and the spraying time is 10 min. Place the sprayed PP bipolar plate in a vacuum drying oven and dry it at 80 °C for 6 h to obtain the multifunctional PP bipolar plate.

[0085] Comparative Example 1 The pretreatment process for the PP bipolar plate is the same as in Example 1.

[0086] The performance of the zinc-bromine flow battery bipolar plate assembled batteries prepared in Examples 1-10 and Comparative Example 1 was tested. The experimental conditions were as follows: the electrolyte was a commercial electrolyte, and the electrode area was 9 cm². 2 The diaphragm is a microporous polyolefin diaphragm with a charge / discharge current density of 20 mA / cm². 2 The charging time was 1 hour, the discharge cutoff voltage was 0.5V, and the positive and negative electrolytes were 50mL. The battery performance tests in the examples and comparative examples were conducted under the same conditions, and the test results are shown in Table 2.

[0087] Table 1. Composition of key components in Examples 1-10 and Comparative Examples 1-3

[0088] Table 2 Comparison of performance test results of zinc-bromine flow batteries prepared in Examples 1-10 and Comparative Examples 1-3

[0089] Table 1 shows the composition of key components in Examples 1-10 and Comparative Examples 1-3; Table 2 compares the performance test results of the bipolar plates prepared in Examples 1-10 and Comparative Example 1 in zinc-bromine flow batteries. As shown in the tables, the coulombic efficiency of the zinc-bromine flow batteries prepared with the zinc-bromine flow electrolyte of this invention is 91.5%-95.6%; the energy efficiency is 75.76%-81.94%; and the voltage efficiency is 82.8%-85.8%. Loading polyaniline on the positive electrode side significantly improves the bromine barrier capacity, accelerates the bromine reaction, and inhibits zinc dendrite formation, thereby improving the coulombic efficiency. Loading cyclodextrin polymer on the negative electrode side significantly inhibits zinc dendrite growth, adjusts the electrolyte pH, inhibits hydrogen evolution reaction, and improves the coulombic efficiency, voltage efficiency, energy efficiency, and cycle stability of the zinc-bromine flow battery.

[0090] Comparing Examples 1-3 and Comparative Example 1, the electrochemical performance data measured when different concentrations of polyaniline solution were used to modify the positive electrode side of the bipolar plate in a zinc-bromine flow battery were all superior to the data measured using the unmodified bipolar plate. Table 2 shows that polyaniline has a significant impact on improving bromine barrier capacity and accelerating the bromine reaction. The table clearly shows that as the concentration of the polyaniline solution increases, the measured electrochemical performance data of the battery are also better, indicating that the concentration of the polyaniline solution has a significant impact on improving bromine barrier capacity and accelerating the bromine reaction.

[0091] Compared with Examples 3-4, Example 3 achieved relatively better overall electrochemical performance, demonstrating that reducing the spraying rate and extending the spraying time can improve the coulombic efficiency, voltage efficiency, and energy efficiency of the zinc-bromine flow battery. This indicates that different spraying rates and times have a profound impact on the performance of the prepared bipolar plate.

[0092] Compared with Examples 3, 5-7, and Comparative Example 1, applying cyclodextrin polymer solutions of different concentrations to the negative electrode side of a bipolar plate with a positive electrode modified by polyaniline resulted in better electrochemical performance data, indicating that the addition of cyclodextrin polymer has a significant impact on the ability of the bipolar plate to suppress zinc dendrites. As can be clearly seen from the table, the measured electrochemical performance data of the battery are better when the concentration of the cyclodextrin solution increases, indicating that the concentration of the cyclodextrin solution has a significant impact on the ability to suppress zinc dendrites.

[0093] Compared with Examples 7-8, Example 7 achieved relatively better overall electrochemical performance, demonstrating that reducing the spraying rate and extending the spraying time can improve the coulombic efficiency, voltage efficiency, and energy efficiency of the zinc-bromine flow battery. This indicates that different spraying rates and times have a profound impact on the performance of the prepared bipolar plate.

[0094] In summary, this invention provides a multifunctional bipolar plate for a zinc-bromine flow battery, its preparation method, and its application. Loading polyaniline onto the positive electrode side of the PP bipolar plate reduces the bromine permeation source and activation energy of the bromine reaction, thereby improving the overall conductivity and comprehensive electrochemical performance (coulombic efficiency, voltage efficiency, and energy efficiency) of the electrolyte, and further reducing the battery's ohmic internal resistance. Modification of the negative electrode side with a cyclodextrin polymer solution of Nafion allows Nafion to stabilize the electrolyte pH, further enhancing the battery's long-term stability and extending its cycle life. The cyclodextrin polymer limits the Zn content. 2+ It can only diffuse in the direction parallel to the substrate, promoting more uniform and dense zinc deposition, reducing the formation of sharp dendrites, and improving electrode stability and cycle life.

[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a multifunctional bipolar plate for a zinc-bromine flow battery, characterized in that, include: 1) Pretreatment of polypropylene bipolar plates; 2) Add polyaniline to a hexadecyltrimethylammonium bromide ethanol solution, stir and sonicate to obtain a mixed solution, spray the mixed solution onto the positive electrode side of the pretreated polypropylene bipolar plate, and dry to obtain a polyaniline-modified polypropylene bipolar plate. 3) Dissolve β-cyclodextrin in NaOH solution, add epichlorohydrin, stir and react, wash until neutral, dry, grind and sieve to obtain cyclodextrin polymer; A cyclodextrin polymer was dispersed in a Nafion solution to obtain a cyclodextrin polymer solution. The cyclodextrin polymer solution was sprayed onto the negative electrode side of a polypropylene bipolar plate modified with polyaniline. After drying, a multifunctional bipolar plate for zinc-bromine flow batteries was obtained.

2. The method for preparing the multifunctional bipolar plate of the zinc-bromine flow battery according to claim 1, characterized in that, In step 1), the pretreatment includes: ultrasonically cleaning the polypropylene bipolar plate with ethanol or deionized water for 15-30 min, and drying it at 40-60℃ for 12-24 h.

3. The method for preparing the multifunctional bipolar plate of the zinc-bromine flow battery according to claim 1, characterized in that, In step 2), the molar concentration of polyaniline in the mixed solution is 0.1-0.3 mol / L.

4. The method for preparing the multifunctional bipolar plate of the zinc-bromine flow battery according to claim 1, characterized in that, In step 2), the stirring time is 30-60 min; the ultrasonic time is 0.5-1.5 h; and the drying conditions are drying at 60-80℃ for 6-12 h.

5. The method for preparing the multifunctional bipolar plate of the zinc-bromine flow battery according to claim 1, characterized in that, In step 2), the spraying conditions include: a spray flow rate of 5-10 mL / min and a spraying time of 5-10 min.

6. The method for preparing the multifunctional bipolar plate of the zinc-bromine flow battery according to claim 1, characterized in that, In step 3), 2.0-6.0 g of cyclodextrin polymer is added to every 100 mL of 5% Nafion solution.

7. The method for preparing the multifunctional bipolar plate of the zinc-bromine flow battery according to claim 1, characterized in that, In step 3), the stirring reaction conditions are: stirring reaction at 50℃ for 16h; the drying conditions are: drying at 80℃ for 12h.

8. The method for preparing the multifunctional bipolar plate of the zinc-bromine flow battery according to claim 1, characterized in that, In step 3), the spraying conditions include: a spray flow rate of 5-10 mL / min and a spraying time of 5-10 min; the drying conditions are: drying at 60-80℃ for 6-12 h.

9. A multifunctional bipolar plate for a zinc-bromine flow battery, characterized in that, The multifunctional bipolar plate for zinc-bromine flow batteries as described in any one of claims 1-8 was prepared.

10. The application of the multifunctional bipolar plate for zinc-bromine flow batteries prepared by the method for preparing the multifunctional bipolar plate for zinc-bromine flow batteries according to any one of claims 1-8 in zinc-bromine flow batteries, characterized in that, The coulombic efficiency of zinc-bromine flow batteries is 91.5%-95.6%; the energy efficiency is 75.76%-81.94%; and the voltage efficiency is 82.8%-85.8%.

Citation Information

Cited By

  • Carbon-plastic bipolar plate of zinc-bromine flow battery as well as preparation method and application of carbon-plastic bipolar plate

    CN122025691A

  • A zinc-bromine flow battery carbon plastic bipolar plate and a preparation method and application thereof

    CN122025691B